L0-Linear Modulus of a Random Linear Operator - Ming Liu; Xia Zhang (Abstract and Applied Analysis)
We prove that there exists a unique L0-linear modulus for an a.s. bounded random linear operator on a specifical random normed module, which generalizes the classical case.